Gambaran Pengetahuan Tentang Seks Bebas Pada Remaja - Endang Sawitri; Wiwin Rohmawati; Endang Wahyuningsih; Fernanda (Stikes Muhammadiyah Klaten, 2022)
Background : Free sex is behavior that arises because of sexual urges. The impact of this free sex can lead to Unwanted Pregnancy and Sexually Transmitted Diseases. The IDHS survey on adolescent reproductive health found that 8.3% of boys and 4.5% of girls had premarital sex. Objective : To find out the description of knowledge about free sex in adolescents. Methods : This research is a quantitative descriptive study. The sampling technique in this research is purposive sampling. The population is 359 students of class X with a sample size of 189 students. The instrument used is demographic data and 17 questions about free sex knowledge filled in via google form. The categories of knowledge are good (75%-100%), sufficient (56%-74%), and poor (<55%). Results and Discussion : The level of knowledge with a good category is the majority of respondents who are female (61.9%), 16 years old (72%) and Muslim (86.2%). Conclusion: The level of knowledge about free sex in the majority of teenagers is good at SMA N 3 Klaten.